A pair of red clogs - Matsuno, Masako; Mizumura, Kazue (Keller, TX : Purple House Press, 2002)
A little Japanese girl tries to hide the fact that she has cracked her new red clogs.
Reprint. Originally published: 1st ed. Cleveland : World Pub. Co., 1960.
Keywords: Shoes -- Juvenile fiction; Japan -- Juvenile fiction